The Page and the Screen: Cinematic Images in the Private Diary of a Young Woman in the Fifties - Laura Busetta (Cinergie)
In the context of studies on “cinephemera”, this contribution aims to investigate the intersections between cinema and private female writing, analyzing some sources usually neglected by historiography. In the context of the contemporary debate on the “writing culture of ordinary people”, I will focus in particular on the private diary. A device that, traditionally, is not intended as a tool for recording cinematic consumption, but is chosen by the writer as a surface of spontaneous self-representation, in which to record daily experiences and personal urgencies. The analysis of an unpublished diary written by a young woman during the years that led to the Italian economic miracle (and preserved at the Archivio Diaristico Nazionale in Pieve Santo Stefano), shows us how female personal writing can also become a means to reflect on family and social roles, on hegemonic values, on behavioral norms,  and on social and consumer practices. The first-person diary becomes a place of interaction with cinematic imagery and star models while, in broader terms, it allows for a reflection on the social experience of cinema, in a historical moment in which it is at the center of the media and consumption system. On the border between public and private issues, the analysis of diary writing favors an “intimate history” of cultural phenomena, which enhances individual “agency” in the analysis and interpretation of broader historical processes.